Threats to Consumers Using Weight on Polish Market of Measuring Instruments - Wiśniewska , Joanna; Matuszak , Leszek; Maleszka , Alicja (Studia Oeconomica Posnaniensia, 2016)
According to European law, producers are responsible for the measuring devices they introduce to the market, and the country's authorities are responsible for activities aiming at minimizing threats connected with using non-conformable goods. Conformity assessment on the market is a kind of market control. State organs control the goods which are placed on the market, identify non-conformable goods, and arrange their withdrawal from circulation or limit accessibility on the market. Measurements are a basic source of information about the condition and characteristics of a product. It is on this basis that products are accepted or rejected. A measuring instrument is one of the elements of the measuring process, and its proper quality characteristics influence the measuring process and its outcome. Threats from non-conformable measuring devices and hazards to consumers are analyzed in the paper on two levels: on the stage of putting devices on market and during their use. The legal aspects of the control over weights brought onto market and put into use are presented in the article. The main goal of the article is analysis of consumers' threats as a result of using non-conformable measuring devices. Public authorities have to describe the priorities to minimize the risk. Therefore, they need to evaluate the range of the risk. The procedure of risk assessment regarding non-automatic scales used in trade is presented in this paper. Risk assessment was done according to a seven-stage procedure. The influence of threats/irregularities on legal interest is identified in a supply chain of non-automatic weights in the Wielkopolska region. Legal interest is widely defined as protection of the consumer, fair play between the manufacturers, confidence in the CE mark indirect confidence of the consumer and producer (manufacturer of the product, the manufacturer's representative, the importer into the EU or other professionals). Based on the threat analysis, which complies with EU guidelines, it is possible to determine the preferential actions for supervision.